Management of major organ involvement of Behçet's syndrome: a systematic review for update of the EULAR recommendations. (13th August 2018) - Ozguler, Yesim; Leccese, Pietro; Christensen, Robin; Esatoglu, Sinem Nihal; Bang, Dongsik; Bodaghi, Bahram; Çelik, Aykut Ferhat; Fortune, Farida; Gaudric, Julien; Gul, Ahmet; Kötter, Ina; Mahr, Alfred; et al.
Abstract: Objective: To assess the efficacy and safety of treatment modalities for major organ involvement of Behçet's syndrome (BS), in order to inform the update of the EULAR recommendations for the management of BS. Methods: A systematic literature review of all randomized controlled trials, controlled clinical trials, or open label trials assessing eye, vascular, nervous system or gastrointestinal system involvement of BS was performed. If controlled trials were not available for answering a specific research question, uncontrolled studies or case series were also included. Results: We reviewed the titles and abstracts of 3927 references and 161 studies met our inclusion criteria. There were only nine randomized controlled trials. Observational studies with IFN-α and monoclonal anti-TNF antibodies showed beneficial results for refractory uveitis. Meta-analysis of case–control studies showed that immunosuppressives decreased the recurrence rate of deep vein thrombosis significantly whereas anticoagulants did not. CYC and high dose glucocorticoids decreased mortality in pulmonary arterial aneurysms and postoperative complications in peripheral artery aneurysms. Beneficial results for gastrointestinal involvement were obtained with 5-ASA derivatives and AZA as first line treatment and with thalidomide and/or monoclonal anti-TNF antibodies in refractory cases. Observational studies for nervous system involvement showed improved outcome with immunosuppressives and glucocorticoids. Meta-analysis of case–control studies showed an increased risk of developing nervous system involvement with ciclosporin-A. Conclusion: The majority of studies related to major organ involvement that informed the updated EULAR recommendations for the management of BS were observational studies.